Comparison of magnetic perturbation data from LEO satellite constellations: Statistics of DMSP and AMPERE. Issue 1 (7th January 2014) - Knipp, D. J.; Matsuo, T.; Kilcommons, L.; Richmond, A.; Anderson, B.; Korth, H.; Redmon, R.; Mero, B.; Parrish, N.
Abstract During the past decade engineering‐grade magnetic field measurements from the low Earth orbiting (LEO) Iridium constellation of communication satellites have been available to the geospace science community as a tool to map field‐aligned currents. The Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE) applied to Iridium measurements markedly improved the temporal and spatial resolution of these data. We developed new methods to compare data from the latest improvement to AMPERE with those from a constellation of four LEO Defense Meteorological Satellite Program (DMSP) spacecraft that carry high‐resolution magnetometers. To perform the comparisons, we transformed all data to a common coordinate frame and altitude (110 km) and developed a means of computing spacecraft magnetic conjunctions. These conjunctions yield discrepancies in the magnetic field perturbations measured at each proximate spacecraft. During the geomagnetic disturbance of 29–30 May 2010, the vector differences in the horizontal perturbations at closest approach (typically a few tens of kilometers) had mean, median, and standard deviation values of 132 nT, 112 nT, and 90 nT, respectively. The DMSP spacecraft tend to report larger perturbations in the northern polar cap and cusp regions, especially during active intervals. We attribute some of the differences to limitations of spacecraft‐attitude knowledge that propagate into AMPERE data. Overall, for the magnetic storm, we provide clear evidence that AMPERE data can provide high‐resolution auroral zone data in good agreement with DMSP data for use in data assimilation algorithms. Such dual‐use commercial data can provide important global augmentation to the nation's space weather monitoring capabilities.